Qualidade da água da sub-bacia do rio Poxim a montante e a jusante da captação da estação de tratamento de água - Jesus, Taynar Mota de (2021)
Water used for human supply must conform to quality requirements and, for this, it is directed to Water Treatment Plants (WTP). In conventional supply water treatment, clarification, filtration, disinfection and fluoridation steps are used. The clarification process, consolidated in the decanters, is responsible for the generation of a greater amount of waste – known as WTP sludge. This, in turn, in accordance with NBR 10.004/2004 and Brazilian Law 12.305/2010, is solid waste and must be disposed of in an environmentally correct manner, and its release into water sources is prohibited. On the other hand, this illegal practice is carried out in Brazil and brings consequences such as the degradation of water aesthetics, siltation of water sources, reduction of photosynthetic activity and ecotoxicity. Similar to what happens in the country, the Poxim WTP, which treat the water collected in the Poxim river sub-basin, does not manage the waste generated and dumps it in the same source, downstream from collection. Therefore, this study evaluated the water quality of the Poxim River before and after the sludge discharge from Poxim WTP. For this purpose, water collections were carried out at the entrance to the WTP and in the river, at a place downstream from the sludge release, as well as from the sludge in a decanter of the station. Thus, tests were carried out to measure the parameters apparent and true color, turbidity, temperature, electrical conductivity, pH, biochemical oxygen demand (BOD), dissolved aluminum, solids, total and thermotolerant coliforms, analyzed in a freshwater methodology based on APHA and ecotoxicity tests (Lactuca sativa as plant bioindicador) based on USEPA. To relate the data, a normality test and a pair test were performed for the points upstream and downstream of the collection, with a confidence level of 95%. Statistical results indicated water degradation along the source for the parameters apparent color, turbidity, dissolved aluminum and thermotolerant coliforms, which may be a consequence of the high suspended solids content of the WTP sludge released into the Poxim river, the high dosage of aluminum sulfate used in the station and the deficiency in sanitary sewage in the Poxim river sub-basin. For the other parameters there was no significant difference between the two points of the Poxim River. Nevertheless, according to CONAMA Resolution No. 357/2005, the stretches of the Poxim River under study are classified in class 4 for the parameters true color, BOD and thermotolerant coliforms, therefore, the use of the spring is not recommended for human supply. Finally, the sludge from Poxim WTP presented much more expressive results than those from water with regard to the apparent color, turbidity and dissolved aluminum parameters. Furthermore, ecotoxicity was found for most of the sludge concentrations used in lettuce seed germination. Thus, it is important to study and apply an environmentally suitable treatment and final disposal solution for this potentially polluting waste.